Perubahan Pondok Pesantren Modern di Perkotaan: Studi Kasus Pondok Pesantren Al-AdzkarTangerang Selatan, Banten - Astuti, Rahma Dani Pudji (UI Scholars Hub, 2017)
In Indonesia, Islamic boarding schools has changed from a traditional boarding school into a modern boarding school. Modern boarding schools customize its label as “Islamic Modern Boarding School” to support a higher cost of educational fees. Based on previous studies, there are findings on competition and commercialization of Islamic educational institutions whereby many Islamic Boarding Schools facilitates dormitories from Santris (Islamic Students). The author argues that the development of middle class Muslims in cities have further supported the commercialization of Islamic education. Even with the strong current of economic commercialization, modern boarding school still maintains spiritual capital as an important aspect of education. This article is written based on a qualitative research in Pondok Pesantren Al-Adzkar, South Tangerang, Banten.